Fieldbook of ibstpi evaluator competencies - Russ-Eft, Darlene F.; Bober-Michel, Marcie J.; Koszalka, Tiffany A.; Sleezer, Catherine (IBSTPI book series., 2013)
The book, Evaluator Competencies: Standards for the Practice of Evaluation, details the development and validation of evaluator competencies by the International Board of Standards for Training, Performance, and Instruction (ibstpi). Developing an understanding of the ibstpi Evaluator Competencies may not be sufficient for individuals to determine how to improve their, or their colleagues', competencies. This Fieldbook provides additional information, resources, and tools to assist those who want to improve their own competencies or those who want to help other individuals improve. Thus, the goals for the present companion volume are: * To provide additional practical information in each of the four evaluator domains (i.e., professional foundations, planning and designing the evaluation, implementing the evaluation plan, and managing the evaluation). * To present practical tools and resources that support specific evaluator competencies, whether as an internal or an external evaluator. * To offer practical insights on the evaluator competencies from experienced evaluators. * To provide practical evaluation exercises and resources that can be used with undergraduate and graduate courses.